PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP TINGKAT KRIMINALITAS DI INDONESIA - Ryan Pratama Audey; Ariusni Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to analyze the effect of factor (X1) on human development index, (X2) unemployment, (X3) population density on crime, in Indonesia. This type of research is descriptive and associative. Data type is secondary data. This study uses panel data with 31 provinces in Indonesia using the Fixed Effect Model (FEM) approach. The results of the study show that (1) the human development index has a significant effect on crime. (2) Unemployment does not have a significant effect on crime. (3) Population density has a significant effect on criminality (4) Taken together there is a significant influence between the human development index, unemployment and population density on crime in Indonesia. Therefore, the government and the authorities are expected to disseminate information to the community about the laws and regulations on criminal offenders and the need to improve education as an effort to improve the quality of Indonesian human resources.